Accuracy of macroscopic examination of gall bladder specimens for malignancy after cholecystectomy - Sharma, Shambhavi; Poudel, Sanjay; Shrestha, Samir; Shah, Surendra; Maharjan, Shanta Bir; Shrestha, Sajan (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Routinely all specimens are sent for HPE due to the possibility of missing incidental gall bladder carcinoma(IGBC) which has a incidence of 0.2-2.9%. Missing IGBC would have a devastating effect on patients. However, many studies have reported thorough macroscopic examination of gallbladder specimen by surgeons would be enough to rule out carcinoma. Those missed carcinomas are at early stage (pT1a) which would not change the management of the patients. Method: It was a prospective observational study that included all patients undergoing cholecystectomy for benign gallstone disease form July 2019 to June 2020 at Patan Academy of Health Sciences. Data collected were analysed using Fisher’s Exact Test. Result: The negative predictive value and specificity of macroscopic examination by surgeons were 99.6% and 84.1% respectively. Incidence of IGBC was found to be 0.31%. Conclusion: Detailed mucosal macroscopic examination of gallbladder specimen by a surgeon can exclude primary malignancy of gall bladder. Therefore, selective approach of HPE after cholecystectomy for benign gallbladder disease can be considered a routine practice.